2022
DOI: 10.1177/00332941211066259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Mental Health and Quality of Life. An Exploratory Study During the First Outbreak in Italy

Abstract: The coronavirus pandemic has been sweeping the world for more than a year. As physical health begins to stabilize in the western world, an increasing concern is related to the impact of the virus and its containment measures on people’s mental health. This work aimed to explore the effect of demographic factors (age, gender, level of education, and socioeconomic status) and variables such as fear of COVID-19 and social support in predicting the quality of life and mental health of adults during the first wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 106 publications
1
8
0
Order By: Relevance
“…In line with previous studies, we found that older age and being female were associated with higher levels of fear [ 7 , 8 ]. Elderly individuals are at higher risk for severe COVID-19 infection [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous studies, we found that older age and being female were associated with higher levels of fear [ 7 , 8 ]. Elderly individuals are at higher risk for severe COVID-19 infection [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Fear has enhanced cautious behaviour, such as social distancing and improved hand hygiene [ 6 ]. However, it has also been associated with factors that deteriorate mental health, such as anxiety [ 6 , 7 ], stress [ 7 ], depression [ 6 , 7 ] and perceptions of decreased quality of life [ 6–8 ]. Greater fear of COVID-19 has been associated with being female, older and lower income [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several studies, the interruption of daily routine had significant consequences for mental health globally [2]. The possibility of infection, as well as the fear of dying or infecting others, had a detrimental impact on people's quality of life and mental health [3]. Studies have also reported that essential workers had a higher risk of anxiety and pandemic-related stress compared to non-essential workers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In families of COVID-19 patients, missing crucial end-of-life care communication with patients could result in long lasting and detrimental effects, including symptoms such as depression and anxiety, and an increased risk of complicated grief (Feder et al, 2021). In general population, especially in the first wave, being at risk of infection, the fear of dying, or the fear of infecting another, has strongly affected individuals' well-being thus impacting on people's quality of life still profoundly challenged by the pandemic and subsequent restrictive measures (Cavazzoni et al, 2022). The focus of the literature on the psychological impacts and interventions of the pandemic era has been mainly directed towards health care workers and special populations (David et al, 2021;Liu et al, 2021;Rodrigues et al, 2021).…”
Section: Rationale and Backgroundmentioning
confidence: 99%